1999
DOI: 10.1094/mpmi.1999.12.3.252
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Characteristics of the nodX Genes from Various Rhizobium leguminosarum Strains

Abstract: We have analyzed the nucleotide sequences of the nodX genes from two strains of Rhizobium leguminosarum bv. viciae able to nodulate Afghan peas (strains A1 and Himalaya) and from two strains of R. leguminosarum bv. trifolii (ANU843 and CSF). The nodX genes of strains A1 and ANU843 were shown to be functional for the induction of nodules on Afghan peas. To analyze the cause of phenotypic differences of strain A1 and strain TOM we have studied the composition of the lipochitin-oligosaccharides (LCOs) produced by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 30 publications
0
17
0
Order By: Relevance
“…trifolii) strains isolated from diverse geographic areas have this gene [58]. nodX encodes for an O-acetyltransferase protein that modifies the Nod factor, permitting rhizobia to form symbiosis both with the "Afghan" (carrying the specific Sym2 A allele of the Nod-factor receptor) and European pea lines [59]. The loss of nodX in the European R. leguminosarum bv.…”
Section: Discussionmentioning
confidence: 99%
“…trifolii) strains isolated from diverse geographic areas have this gene [58]. nodX encodes for an O-acetyltransferase protein that modifies the Nod factor, permitting rhizobia to form symbiosis both with the "Afghan" (carrying the specific Sym2 A allele of the Nod-factor receptor) and European pea lines [59]. The loss of nodX in the European R. leguminosarum bv.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, both synthetic Nod factors and the chitin pentamer PACT, which is unable to provoke Had on G. soja, induced the transient accumulation of Enod40 mRNA. It would thus seem that not only are absolute levels of Nodfactors important but also the composition and relative proportions of the mixtures excreted by rhizobia are necessary for the induction of different components of the nodulation pathway (190).…”
Section: Nod Factors and Host Specificitymentioning
confidence: 99%
“…Presence of Sym2 A in homozygous state leads to block of infection thread progression in the root hair, similarly to phenotype of sym37 mutants [55]. Later it was shown that Rlv strains able to nodulate "Afghan" cultivars have special gene called nodX, which is involved in the modification of NF structure [116,117]. NodX encodes the acetyltransferase providing O-acetylation on reducing end of NF sugar backbone.…”
Section: Pea (Pisum Sativum L) As a Unique Example Of Increased Specmentioning
confidence: 95%